Drainless robot-assisted minimally invasive oesophagectomy - randomized controlled trial (RESPECT) - Müssle, Benjamin; Kirchberg, J.; Buck, N.; Radulova-Mauersberger, O.; Stange, D.; Richter, T.; Müller, Beat P.; Klotz, Rosa; Larmann, Jan; Korn, Stephanie; Klimova, A.; Grählert, X.; et al. (Trials, 2023)
Background: The purpose of this randomized trial is to evaluate the early removal of postoperative drains after robot-assisted minimally invasive oesophagectomy (RAMIE). Evidence is lacking about feasibility, associated pain, recovery, and morbidity. Methods/design: This is a randomized controlled multicentric trial involving 72 patients undergoing RAMIE. Patients will be allocated into two groups. The “intervention” group consists of 36 patients. In this group, abdominal and chest drains are removed 3 h after the end of surgery in the absence of contraindications. The control group consists of 36 patients with conventional chest drain management. These drains are removed during the further postoperative course according to a standard algorithm. The primary objective is to investigate whether postoperative pain measured by NRS on the second postoperative day can be significantly reduced in the intervention group. Secondary endpoints are the intensity of pain during the first week, analgesic use, number of postoperative chest X-ray and CT scans, interventions, postoperative mobilization (steps per day as measured with an activity tracker), postoperative morbidity and mortality. Discussion: Until now, there have been no trials investigating different intraoperative chest drain strategies in patients undergoing RAMIE for oesophageal cancer with regard to perioperative complications until discharge. Minimally invasive approaches combined with enhanced recovery after surgery (ERAS) protocols lower morbidity but still include the insertion of chest drains. Reduction and early removal have been proposed after pulmonary surgery but not after RAMIE. The study concept is based on our own experience and the promising current results of the RAMIE procedure. Therefore, the presented randomized controlled trial will provide statistical evidence of the effectiveness and feasibility of the “drainless” RAMIE.
Gesehen am 23.06.2023